Single PON network design with unconstrained splitting stages - Lopes, M. J.; L. Gouveia; Sousa, A. (2014 INFORMS Telecommunications Conference, 2014)
A Passive Optical Network (PON) is a network technology for deploying access networks based on passive optical components. In a single PON access network, the client terminals are connected to a Central Office through optical splitters and interconnecting fibers where each splitter splits the input optical signal coming from the Central Office over its different output ports. In this paper, we consider a PON topology where the splitting ratio and the number of splitting stages is not constrained to a given target design but, instead, are decided based on the cost of the network solution. We present different Integer Linear Programming formulations to model this problem and provide computational results showing that the optimal solutions can be computed for realistic problem instances. In addition, we show how the formulations can be adapted for the traditional PON topology approaches and present computational results showing that significant cost gains can be obtained with the unconstrained splitting stage approach.